Neurogenic Heterotopic Ossification of the Hip: a Case Report - Çelik, M; Başaran, S. H (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
Heterotopic ossification (HO) denotes aberrant osteogenesis in extra-skeletal tissues, often associated with neurological disorders, total hip arthroplasty, and specific traumatic scenarios. Neurogenic heterotopic ossification manifests prominently subsequent to traumatic brain injury or spinal cord injury, with Guillain-Barre Syndrome presenting an infrequent etiological link. This article details the case of a 56-year-old female diagnosed with Guillain-Barre Syndrome, who developed neurogenic heterotopic ossification around both hips within two years of disease onset. The patient's medical history included mechanical ventilation, incomplete tetraplegia, and prolonged immobilization. A conclusive diagnosis of HO was established through radiological and clinical assessments. After neurogenic heterotopic ossification was confirmed, the patient had surgery to remove the lesions, radiation therapy, and medication treatments as planned. Physical therapy was introduced one week post-surgery, with subsequent follow-ups tracking improvements in pain levels, range of motion (ROM), and Activities of Daily Living scores. Key words: neurogenic heterotopic ossification, Guillain-Barre syndrome, hip, excision.
Keywords: Range of Motion, Articular; heterotopická osifikace; lidé středního věku; Guillainův-Barrého syndrom; rozsah kloubních pohybů; Ossification, Heterotopic; Middle Aged; Guillain-Barre Syndrome; Hip Joint; Humans; lidé; ženské pohlaví; Female; kyčelní kloub